Hot Brownian motion and photophoretic self-propulsion - Schachoff, Romy; Selmke, Markus; Bregulla, Andreas; Cichos, Frank; Rings, Daniel; Chakraborty, Dipanjan; Kroy, Klaus; Günther, Katrin; Henning-Knechtel, Anja; Sperling, Evgeni; et al. (Diffusion Fundamentals, 2015)
We describe the motion of heated particles in a simple liquid, for which we can theoretically derive generalized fluctuation-dissipation relations that hold far from equilibrium, as we demonstrate both experimentally and via molecular-dynamics simulations. Due to persistent laser-light absorption, these particles excite a radially symmetric or asymmetric (Janus particles) temperature profile in the solvent, which affects their random (Brownian) and systematic (self-phoretic) motion. In case of a radially symmetric temperature profile, we show that the particles perform “hot Brownian motion” (HBM), with different effective temperatures pertaining to their various degrees of freedom. We moreover predict and experimentally observe a peculiar dependence of their diffusivity on the particle size. In case of an asymmetric temperature profile, we find a superimposed self-phoretic directed motion. To adjust the importance of this “active” motion relative to the random hot Brownian motion, the shape of the particle is modified by binding DNA molecules and DNA origami to Janus beads. The persistence of the directed transport can thereby greatly be enhanced.